(untitled) (Журналистика сериясы, 2016)
The paperis devoted to the description of a mythichero in the Pental-ogy about the Leathers to cking Talesby J.F. Cooper. The paper analyses the divergence in concerns and intentions between J.F.Cooper’s Leather-stocking Tales and the remainder of his works. Such divergence has led many scientists to perceive “two Coopers” instead of one. By tracing the development of the hero within this novel, this article attempts to recon-cile these divengencies; realize the fullness of the myth; and isolate the principal concern which informs all of J.F.Cooper’s work. It is necessary to note that the works of James Fenimore Cooper have long widespread popularity. But critics are divided about the nature of J.F.Cooper’s strength and achievement. This situation derives largely from the fact that differ-ent works within his corpus appear to have little in common. Much of his writing, such as “The American Democrat” and “Home as Found”, has the appearance of hard-headed political and social comment. On the other hand, the Leatherstocking Tales stand out as an example of lyrical beauty which seem totally removed from his other works.